Calculation of Meshing Backlash for Cycloidal-pin Gear of RV Reducer Under the Influence of Tooth Profile Deviation - Tianxing Li; Guofeng Wang; Xiaotao An; Chunrong Xing; Meng Tian (Jixie chuandong)
The meshing backlash of cycloidal-pin gear has a great influence on the meshing transmission performance and motion accuracy of RV reducer, so the accurate calculation of meshing backlash is an important content in the study of contact characteristics of cycloidal-pin gear. At present, the calculation of meshing backlash in China is mostly based on theoretical design of tooth profile, without considering the tooth profile deviation of cycloidal gear in the process of modification design and processing, so the calculated theoretical meshing backlash is inconsistent with the actual meshing backlash. For this, a new method for calculating the meshing backlash of cycloidal-pin gear is proposed, considering the influence of tooth profile deviation. The real meshing backlash of cycloidal-pin gear is obtained from the point of view of engineering and mathematics. By effectively superimposing the tooth profile errors of cycloidal gear on the theoretical tooth profile, the digitized tooth surface with high approximation to the actual machined tooth surface is reconstructed based on non-uniform rational NURBS. According to the established contact analysis model of cycloidal-pin gear transmission, the minimum distance between the center of the pin tooth and the tooth profile of cycloidal gear is calculated by differential geometry principle. The accurate meshing backlash under the influence of tooth profile error is obtained, which provides a new idea for the transmission performance research and tooth profile modification design of cycloidal-pin gear pair of RV reducer.